2012
DOI: 10.1117/12.906207
|View full text |Cite
|
Sign up to set email alerts
|

Sensing cocaine in saliva with attenuated total reflection infrared (ATR-IR) spectroscopy combined with a one-step extraction method

Abstract: On-site drug tests have gained importance, e.g., for protecting the society from impaired drivers. Since today's drug tests are majorly only positive/negative, there is a great need for a reliable, portable and preferentially quantitative drug test. In the project IrSens we aim to bridge this gap with the development of an optical sensor platform based on infrared spectroscopy and focus on cocaine detection in saliva. We combine a one-step extraction method, a sample drying technique and infrared attenuated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…If the oral fluid sample was extracted right after the collection and preparation of the sample, a good reproducibility could be observed. It was concluded that this method not only allowed to reach a LOD of 10 mg/L or lower after extraction in PCE (see table 2), but also allowed to overcame the problem of concentration changes due to the small variations in the dried sample pattern [31].…”
Section: Ir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…If the oral fluid sample was extracted right after the collection and preparation of the sample, a good reproducibility could be observed. It was concluded that this method not only allowed to reach a LOD of 10 mg/L or lower after extraction in PCE (see table 2), but also allowed to overcame the problem of concentration changes due to the small variations in the dried sample pattern [31].…”
Section: Ir Spectroscopymentioning
confidence: 99%
“…Hence, the employment of bidimensional NMR appears a promising tool to improve the technique and then to be able to determine the presence of illicit drugs in oral fluid. 31 Spectroscopic methods appear to be an excellent combination of fast and non-destructive tools, although until now they have been scarcely used for drugs detection in oral fluid. Actually, they still need improvements to be applied for the determination of a wide range of drugs in real samples and to be of real interest for clinical and forensic applications.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation